Культурология: практикум; учебное пособие - Бабаева А. В. Анастасия Валентиновна; Глуздов В. А. Виктор Андреевич; Касьян А. А. Андрей Афанасьевич; Фортунатова В. А. Вера Алексеевна; Шапошников Л. Е. Лев Евгеньевич (Москва, Высшая школа, 2006)
Авторы указ. на обороте тит. л.